Adaptive Educational Social Work in Vocational Batik Learning for Students with Disabilities: A Qualitative Case Study - Wiwit Widiansyah; Jajat S. Ardiwinata; Mustofa Kamil; Asep Saepudin; Maulani Zahra Febriyana (Journal of Nonformal Education, 2026)
Background – Students with disabilities require accessible vocational learning that connects practical competence, cultural participation, and emerging independence. SLB Negeri Cilacap uses batik production as a school-based vocational context. Research Urgency – Evidence remains limited on how culturally grounded vocational practice can be adapted through an educational social work support system within a special school. Research Objectives – This study examined instructional adaptations, reported and observed learner development, and the relational and material conditions shaping Grade XI vocational batik learning. Research Method – A single-case qualitative study involved 13 purposively selected participants: five educators and trainers, six students with hearing, communication, or intellectual disabilities, and two parents. Data came from interviews, direct observation, and program documents. The analysis organized evidence across participant groups and data sources, supported by triangulation and member checking. Research Findings – Educators used visual demonstration, tangible tools, simple language, repetition, individual guidance, and process-focused reinforcement. Observations and participant accounts indicated developing knowledge, greater control during canting and coloring, and emerging patience, responsibility, cooperation, confidence, and initiative. Development remained uneven. Limited equipment, practice time, environmental comfort, fear, fatigue, and informal coordination constrained participation. Research Conclusion – Adaptive instruction and relational support operated together, but the single-case design does not establish causal effectiveness, sustained competence, or transferability. Research Novelty/Contribution – The study proposes a provisional framework linking needs assessment, adaptive planning, guided culturally grounded practice, psychosocial support, and iterative capability monitoring.